Genetics and Genomics of Gastroschisis, Elucidating a Potential Genetic Etiology for the Most Common Abdominal Defect: A Systematic Review - John P. Marquart; Qian Nie; Tessa Gonzalez; Angie C. Jelin; Ulrich Broeckel; Amy J. Wagner; Honey V. Reddi (Journal of Developmental Biology)
(1) Background: The exact etiology for gastroschisis, the most common abdominal defect, is yet to be known, despite the rising prevalence of this condition. The leading theory suggests an increased familial risk, indicating a possible genetic component possibly in the context of environmental risk factors. This systematic review aims to summarize the studies focused on the identification of a potential genetic etiology for gastroschisis to elucidate the status of the field. (2) Methods: Following the PRISMA-ScR method, Pubmed and Google Scholar were searched, and eligible publications were mined for key data fields such as study aims, cohort demographics, technologies used, and outcomes in terms of genes identified. Data from 14 human studies, with varied cohort sizes from 40 to 1966 individuals for patient vs. healthy controls, respectively, were mined to delineate the technologies evaluated. (3) Results: Our results continue the theory that gastroschisis is likely caused by gene–environment interactions. The 14 studies utilized traditional methodologies that may not be adequate to identify genetic involvement in gastroschisis. (4) Conclusions: The etiology of gastroschisis continues to remain elusive. A combination of omics and epigenetic evaluation studies would help delineate a possible genetic etiology for gastroschisis.